A atuação da palavra no desenvolvimento psicogenético do sujeito surdo e seu atendimento psicoterápico: neurose, plasticidade cerebral e outros abismos - Camargos, Gláucio Silva (2018)
The speech is one of the main instruments of psychotherapy, which represents an obstacle to the treatment of congenital deaf who do not use oral language to symbolize their mental states. Objective: To analyze the process of psychic construction in deaf subjects using sign language, their relation with their linguistic development and to indicate possible considerations for the psychotherapeutic work with this population. Methods: We carried out a bibliographical survey through a systematic review based on the Prisma method. After that, we performed a multiple case study through a psychotherapy program designed to attend three deaf individuals with congenital deafness in the deaf community of São José do Rio Preto -SP, selected by lot, from a private clinical record. The program was structured in twenty-six sessions of dynamic psychotherapy. The sessions were held individually and systematically, aiming to observe the patterns in the development of mental processes, performed once a week, lasting 50 minutes. For data analysis we used SPINK's Maps and Association Trees (2010). Results: Differences in the semiotic language system in congenital deaf people result in adaptations in the psychic development of these subjects due to the nature of sign language. Conclusion: Psychotherapeutic treatment for the deaf should take into account their own semiotic system, their symbolic organization, and their culture.